The development and validation of the Growing Disciples Inventory (GDI) as a curriculum-aligned self-assessment for Christian education - Bradfield, Glynis Madeleine (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD)--University of Stellenbosch, 2011.